The Effects of Poor Drainage System in Batam Road: A Case in Nagoya, Batam - Jonathan Jonathan; Mulia Pamadi (LEADER: Civil Engineering and Architecture Journal, 2023)
The poor drainage system is a big issue for giving good road construction quality. Because the beneath is a drainage system. Batam City is the fastest growing city in transportation wise, but the hydrological cycle creates floods in areas that have poor systematical performance. Despite its importance, the assessment of the Effects Poor Drainage System in Batam is far from enough. Sub-district Nagoya in Batam City is chosen as the research area due to having a poor drainage system and flooding when heavy rain falls. To assess this research, a survey is conducted on the field. The data is achieved by the qualitative method and compared the effectiveness of drainage systems to other advanced countries with great drainage systems. The result is shown that Batam City is far from having proper systematical drainage due to the buildup of garbage and sedimentation by sand and soil. Hence this still could result from overflow and cover the road pavements that could lead to a domino effect by scraping the asphalt aggregates, creating damages and effects such as potholes, puddles, traffic congestion, and accidents in the driveway.